2014
DOI: 10.5032/jae.2014.02167
|View full text |Cite
|
Sign up to set email alerts
|

Educating the Future of Agriculture: A Focus Group Analysis of the Programming Needs and Preferences of Montana Young and Beginning Farmers and Ranchers

Abstract: In presenting this thesis in partial fulfillment of the requirements for a master's degree at Montana State University, I agree that the Library shall make it available to borrowers under rules of the Library.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Chalofsky, 1999;Stewart & Shamdasani, 2014) and agricultural education literature more specifically (e.g. Bailey, Arnold, & Igo, 2014). A total of 28 individuals participated in the three focus groups; 10 individuals from NIFA, 10 individuals from UT, and eight individuals from PVAM.…”
Section: Methodsmentioning
confidence: 99%
“…Chalofsky, 1999;Stewart & Shamdasani, 2014) and agricultural education literature more specifically (e.g. Bailey, Arnold, & Igo, 2014). A total of 28 individuals participated in the three focus groups; 10 individuals from NIFA, 10 individuals from UT, and eight individuals from PVAM.…”
Section: Methodsmentioning
confidence: 99%
“…This is seen in the concept of "demonstration effects," which holds that engagement with environmentally beneficial farming practices is diffused through informal observation (Makita 2016). Several studies have found a preference among beginning farmers for experiential learning in group settings that emphasize social networks (Trede 2000;Bailey et al 2014). Finally, there is a need to understand the biophysical impacts related to this research (Reimer et al 2014).…”
Section: Percentage Of Totalmentioning
confidence: 99%
“…In the 2012 census, 34% of beginning farmers had a four-year college degree com-pared to 24% of established farmers (USDA 2017). Beginning farmers are also more likely to seek continuing education opportunities than established farmers (Bailey et al 2014).…”
mentioning
confidence: 99%
“…Bailey, Arnold, and Igo (2014) found social media was highly utilized by their participants to stay current on educational events and information. Additionally, younger farmers and ranchers find value in networking with older producers, leaders in agriculture, and peer producers because it can serve as an educational experience (Bailey et al, 2014). Despite some logistical and technological difficulties, exhibitors had positive perceptions of the 20th Annual Taste.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%